Prevalence of Undernutrition and Associated Factors among Lactating Mothers of Angecha District, Kembata Tembaro Zone, Southern Ethiopia - Moges Muluneh Boke; Aman Yesuf; Befikadu Tariku Gutema (Journal of Nutrition and Metabolism)
Background. Major reasons for malnutrition, particularly among those who live in low- and middle-income countries, are physiological vulnerability and inadequate intake. The objective of the study was to assess the prevalence of undernutrition and associated factors among lactating mothers of Angecha District, Southern Ethiopia. Methods. A community-based cross-sectional study was conducted among randomly selected lactating mothers in Angecha District from March to April 2017. A pretested structured questionnaire was used to assess the prevalence of undernutrition and associated factors among lactating mothers. Undernutrition was defined as the body mass index of less than 18.5 kg/m2. A multivariable logistic regression model was fitted, and the adjusted odds ratio (AOR) at a p value less than 0.05 was used to determine a statistically significant association between predictors and outcome variables. Result. The prevalence of undernutrition among lactating mothers was 21.2% (95% CI: 17.52, 25.46). The odds of undernutrition were higher among lactating mothers in the younger age group (AOR 4.12 (95% CI: 1.25–13.63), compared to 36–49 years group), dietary diversity less than five food groups (AOR 2.4, 95% CI: 1.35–4.36), and not attending antenatal care (ANC) (AOR 2.90 (95% CI: 1.43–5.86), compared to those who attended ANC for 4 or more times). The odds of undernutrition among lactating women from 3rd quantile wealth index households reduced by nearly half (AOR 0.47, 95% CI: 0.23–0.98) compared to lactating mothers from 1st quantile wealth index households. Conclusion. Nearly one in every five lactating mothers was undernourished. Age, dietary diversity score, ANC visit, and wealth index were found to be the associated factors of undernutrition. Therefore, due attention should have to be given to increase the use of ANC.